2018
DOI: 10.1128/mbio.01694-18
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Proteasome Recognition of the mRNA-Binding Protein Cth2 Facilitates Yeast Adaptation to Iron Deficiency

Abstract: Iron is a vital element for many metabolic pathways, including the synthesis of DNA and proteins, and the generation of energy via oxidative phosphorylation. Therefore, living organisms have developed tightly controlled mechanisms to properly distribute iron, since imbalances lead to nutritional deficiencies, multiple diseases, and vulnerability against pathogens. Saccharomyces cerevisiae Cth2 is a conserved mRNA-binding protein that coordinates a global reprogramming of iron metabolism in response to iron def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Cth2 also limits the accumulation of iron into the vacuole when iron levels are low by promoting the degradation of the CCC1 transcript encoding for the vacuolar iron importer (Puig et al, 2005). The overexpression of a functional CTH1 or CTH2 gene is highly cytotoxic (Thompson et al, 1996;Pedro-Segura et al, 2008;Romero et al, 2018b), so yeast cells have to tightly control their expression. Interestingly, both mRNAs contain AREs that allow a negative cross-and auto-regulation that limits their expression and that is important for the activation of respiration and for optimal adaptation to the transit from iron-deficient to iron-sufficient conditions (Martinez-Pastor et al, 2013b).…”
Section: Post-transcriptional Remodeling Of Iron Metabolism By the Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…Cth2 also limits the accumulation of iron into the vacuole when iron levels are low by promoting the degradation of the CCC1 transcript encoding for the vacuolar iron importer (Puig et al, 2005). The overexpression of a functional CTH1 or CTH2 gene is highly cytotoxic (Thompson et al, 1996;Pedro-Segura et al, 2008;Romero et al, 2018b), so yeast cells have to tightly control their expression. Interestingly, both mRNAs contain AREs that allow a negative cross-and auto-regulation that limits their expression and that is important for the activation of respiration and for optimal adaptation to the transit from iron-deficient to iron-sufficient conditions (Martinez-Pastor et al, 2013b).…”
Section: Post-transcriptional Remodeling Of Iron Metabolism By the Mrmentioning
confidence: 99%
“…The higher relevance of Cth2 in the adaptation of yeast cells to iron depletion is highlighted by the growth defect that cth2 Δ mutant cells display under these conditions, which is exacerbated in cth1 Δ cth2 Δ double mutants ( Puig et al, 2005 ). Cth2 is a highly unstable nucleocytoplasmic shuttling protein ( Vergara et al, 2011 ; Romero et al, 2018b ). A nuclear localization signal (NLS) embedded in its TZF motif enables its import to the nucleus, where it co-transcriptionally associates to ARE-containing mRNAs ( Prouteau et al, 2008 ; Vergara et al, 2011 ).…”
Section: Regulation In Response To Iron Deficiencymentioning
confidence: 99%
“…We reported that Hrr25 is a negative regulator of the transcriptional activator Haa1, which is important in cellular adaptation to acetic acid stress (COLLINS et al 2017). Hrr25 has also been reported to regulate Cth2, an RNA-binding protein that plays an important role in iron hemostasis (ROMERO et al 2018). Phosphorylation of Cth2 by Hrr25 leads to Cth2's recognition by the SCF Grr1 E3 ubiquitin ligase and degradation via the 26S proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors could participate in this regulation. For instance, the E3 ubiquitin ligase complex SCF Grr1 , which positively regulates RTG signaling by promoting the ubiquitination and degradation of the Rtg1/Rtg3-inhibitor protein Mks1, has been recently implicated in the degradation of the iron-regulated protein Cth2, and grr1Δ cells are unable to grow in iron-deficient conditions [36].…”
Section: Discussionmentioning
confidence: 99%